Difficulties and prospects for the development of high-tech projects in the epoch of digital transformation of economy - I. A. Mandych; A. V. Bykova (Российский технологический журнал)
It is now customary to talk about the increasing role of high-tech projects in the formation of a digital model of the Russian economy. And the breakthrough that occurred at the turn of the century is called the information revolution. The task of developing an innovative economy in Russia is to ensure conditions under which the volume of production of science-intensive products, the share of which is extremely low, will increase. The production of these products is carried out by high-tech projects requiring financial, informational and resource support from various institutions, including the state. Today, Russia has a high level of potential for innovative development in the global economic space, however, at the moment, it does not contribute to its implementation. The aim of the scientific article is the formation of a new model of state support for the development of the industry of high-tech projects, which are the basis of the information, digital and innovative economy. The relevance of the research on the selected topic is due to the fact that in modern times there is a digital transformation of the economy of the Russian Federation (RF), which requires decisionmaking on the formation of a new approach to participation in high-tech projects programs. Within the framework of the article, the following tasks were solved: trends in the development of the innovative economy of Russia and its key problems in the framework of supporting high-tech projects were considered and recommendations were made on the formation of a new model of state support for the development of high-tech projects based on the study and borrowing of foreign experience of advanced countries of the digital economy, including the USA, Germany and Japan.